Relationship between laser-generated micro- and nanostructures and the long-term stability of bonded epoxy-aluminum joints - Freund, Jonathan; Löbbecke, Miriam; Delp, Alexander; Walther, Frank; Wu, Shuang; Tröster, Thomas; Haubrich, Jan (The Journal of Adhesion)
To improve the mechanical performance and to address current shortcomings of adhesive bonds such as bond degradation due to aging, a pulsed laser surface pretreatment of the metal surfaces of aluminum AW 6082-T6 joints with epoxy adhesive E320 is investigated. The surface treatment of the specimens resulted in increased single-lap shear (SLS) strengths before and after hydrothermal aging in 80°C hot water compared to nonpretreated reference specimens. In order to reveal the correlations of laser parameters, resulting surface morphologies and the SLS strength, differently laser pretreated surfaces were characterized at the micro- and nanoscale using optical and scanning electron microscopies. The surface enlargement was quantified with a digital image analysis of cross-sections prepared from the joint interfaces. An analysis of variances (ANOVA) of the SLS results indicated that the laser parameters power and pulse frequency were most critical for obtaining high SLS strengths. Pretreated joint surfaces with a high micro- and nano-surface enlargement and deep solidification structures provide high SLS strengths of up to 50 MPa and almost negligible aging losses of merely 4%. Undercut structures on the pretreated surfaces were found to be beneficial for the mechanical and aging properties when only limited micro- and nanostructuring was applied.
Keywords: Materials Chemistry; Surfaces; Coatings and Films; Surfaces and Interfaces; Mechanics of Materials; General Chemistry

Transferability of the Structure–Property Relationships from Laser-Pretreated Metal–Polymer Joints to Aluminum–CFRP Hybrid Joints - Freund, Jonathan; Lützenkirchen, Isabel; Löbbecke, Miriam; Delp, Alexander; Walther, Frank; Wu, Shuang; Tröster, Thomas; Haubrich, Jan (Journal of Composites Science)
The transferability of structure–property relationships for laser-pretreated metal adhesive joints to laser-pretreated metal–carbon-fiber-reinforced plastic (CFRP) bonds was investigated. Single-lap shear tests were performed on hybrid AW 6082-T6–CFRP specimens pretreated with the same pulsed laser surface parameter sets on the metal surface as previously tested, AW 6082-T6–E320 metal adhesive joints. The fracture surfaces were characterized to determine the type of failure and elucidate differences and commonalities in the link between surface structures and single-lap shear strengths. Digital image analyses of the hybrid specimens’ fractured surfaces were used to quantify remaining CFRP fragments on the metallic joint side. The results indicate that high surface enlargements and the presence of undercut structures lead to single-lap shear strengths exceeding 40 MPa and 35 MPa for unaged and aged hybrid specimens, respectively. Whereas for the metal–polymer joints, the trend from high strength to weakly bonded specimens is largely continuous with the degree of surface structuring, hybrid metal–CFRP joints exhibit a drastic drop in joint performance after aging if the laser-generated surface structures are less pronounced with low surface enlargements and crater depths. Surface features and hydrothermal aging determine whether the specimens fail cohesively or adhesively.

Adhesion properties of the hybrid system made of laser-structured aluminium EN AW 6082 and CFRP by co-bonding-pressing process - Wu, Shuang; Delp, Alexander; Freund, Jonathan; Walther, Frank; Haubrich, Jan; Löbbecke, Miriam; Tröster, Thomas (The Journal of Adhesion)
A parameter investigation for manufacturing a hybrid system through the prepreg pressing process was carried out within the scope of this work to achieve optimal adhesion properties. The hybrid specimen comprises an aluminium sheet of alloy EN AW 6082 in T6 condition and a thermoset Carbon Fibre Reinforced Plastics prepreg. The prepreg pressing process allows the curing reaction of epoxy resin and the joining process to occur simultaneously to avoid an additional bonding process step. The surface of the aluminium sheet was pretreated in advance using a pulsed Nd:YAG laser to enhance the bonding properties. In the first step, the shear edge tests investigated the adhesion properties achieved with different consolidation (temperature, time and pressure) and laser parameters. Then, 3-point bending tests were carried out to investigate the influence of the consolidation parameters on the mechanical properties of the Carbon Fibre Reinforced Plastics-laminate. In this way, the optimal parameter sets for manufacturing hybrid structures were determined.
Keywords: Materials Chemistry; Surfaces; Coatings and Films; Surfaces and Interfaces; Mechanics of Materials; General Chemistry

Intrinsic forming of hybrid parts made of laser-structured aluminium sheet and CFRP-Prepreg - Wu, Shuang; Freund, Jonathan; Delp, Alexander; Haubrich, Jan; Löbbecke, Miriam; Walther, Frank; Tröster, Thomas
This paper introduces an intrinsic manufacturing process of a hat profile made of laser-pretreated aluminium sheet of alloy EN AW-6082 in T6 condition and carbon fibre-reinforced plastic (CFRP) prepreg. The resin system used in combination with CFRP was epoxy resin (EP). Before manufacturing, the laser-pretreated aluminium sheet and CFRP prepreg were stacked to form a multi-layer composite, which was pressed simultaneously in one process step. The optimal CFRP layer structure was calculated in advance using the finite element method. During the forming process, the curing reaction and the joining of the aluminium sheet and CFRP prepreg will take place simultaneously. Thus, further joining techniques such as bonding and riveting could be saved, and a much more efficient process could be achieved. After manufacturing, shear-edge test was used to characterize the adhesion properties of the hybrid part.

Feedbackverhalten frühpädagogischer Fachkräfte in mathematischen Spielsituationen – Ergebnisse einer clusteranalytischen Typisierung Feedback behaviour of early childhood teachers in mathematical play situations - results of a cluster analysis - Aumann, Lena; Graf-König, N.; Puca, R. M.; Gasteiger, H. (Zeitschrift für Grundschulforschung)
Zusammenfassung Kinder erhalten in der Kindertagesstätte täglich Feedback, das je nach Feedbackart (z. B. personen-/prozessbezogen) unterschiedlich auf Lernen und Motivation wirken kann. Bislang ist wenig untersucht, ob es (z. B. analog zu Erziehungsstilen) fachkrafttypisches Feedbackverhalten gibt. In dieser Studie wurde das Feedbackverhalten frühpädagogischer Fachkräfte ( N = 43) in mathematischen Spielsituationen mit insgesamt 143 Kindern ausgewertet. Clusteranalytisch wurden fünf Fachkrafttypen ermittelt. Diese unterscheiden sich in der Menge und Spezifität des genutzten Feedbacks und darin, inwieweit sich spezifisches Feedback auf das Ergebnis oder den Prozess bezieht. Die Erkenntnisse können sowohl für die Erforschung der Auswirkungen von Feedback als auch im Rahmen von Fortbildungen genutzt werden.

Mikroformen des Praxisbezugs im Lehramtsstudium in NRW. Eine Bestandsaufnahme anhand der bildungswissenschaftlichen Studienanteile des Studiengangs HRSGe - Homt, Martina (die hochschullehre)
Im Zusammenhang mit dem Lehramtsstudium wird häufig ein mangelnder Praxisbezug kritisiert und dabei vornehmlich auf schulische Praxisphasen als sogenannte Makroformen des Praxisbezugs rekurriert. Eine Auseinandersetzung mit Mikroformen auf der curricularen Ebene findet hingegen kaum statt. Um einen Überblick über Mikroformen des Praxisbezugs zu erhalten, wird unter Rück griff auf Zielperspektiven der Lehrkräftebildung ein Analyserahmen mit den Kategorien Praxis als Bezugspunkt von Themen, Praxis als Gegenstand der Auseinandersetzung mit Themen, Praxis als Gegenstand von Erprobung sowie Praxis als Gegenstand von Analyse und Reflexion entwickelt und auf das intendierte Curriculum der lehramtsausbildenden Hochschulen in NRW in Form von Prüfungsordnungen als rahmensetzende Grundlage für die Planung von Studienangeboten angewandt. Die inhaltsanalytische Auswertung zeigt, dass alle Kategorien in den Prüfungsordnungen thematisiert werden, jedoch in unterschiedlicher Intensität. Die Befunde werden mit Blick auf die Zielperspektiven des Lehramtsstudiums, die begriffliche Unschärfe von Praxisbezug sowie Konsequenzen für die Ausgestaltung des Studienangebots auf Ebene des implementierten Curriculums diskutiert.

Forschungsperspektiven und -befunde zum Forschenden Lernen im Praxissemester. Plädoyer für eine Zielklärung - Bloh, Bea; Homt, Martina (PraxisForschungLehrer*innenBildung. Zeitschrift für Schul- Und Professionsentwicklung. (PFLB))
Die mit dem Forschenden Lernen verbundenen Verständnisse werden in der Literatur als vielfältig bewertet und die damit einhergehenden Auswirkungen als problematisch für Erforschung, hochschuldidaktische Umsetzung sowie Wirkungsannahmen gesehen (Huber & Reinmann, 2019). Vornehmlich in der Lehrkräftebildung entwickelte sich ein eigener Diskurs. Im vorliegenden Aufsatz wird dafür plädiert, die immer wieder benannte spezifische, berufsperspektivische Zielsetzung des Forschenden Lernens in der Lehrkräftebildung stärker theoretisch auszuformulieren, um die Verständnisklärung von Forschendem Lernen vor diesem Hintergrund vorantreiben zu können. Damit einhergehend werden aktuelle Forschungsbefunde und -erkenntnisse des Forschenden Lernens im Praxissemester in Deutschland berichtet und diskutiert. Es werden mögliche Ansatzpunkte für die theoretische Weiterentwicklung und damit verbundene Implikationen für die Praxis aufgezeigt.

Die Nutzung von (Evidenz-)Quellen im Referendariat - Homt, Martina; Bloh, Bea

Beste Bedingungen für junge Ökonominnen und Ökonomen? Neue Daten und Empfehlungen der Arbeitsgruppe 'Nachwuchs' im Verein für Socialpolitik - Bayer, Christian; Englmaier, Florian; Riphahn, Regina; Schmidt-Dengler, Philipp; Sondergeld, Virgina; Sureth-Sloane, Caren; von Wangenheim, Jonas; Weizsäcker, Georg (Perspektiven der Wirtschaftspolitik)
Der Verein für Socialpolitik hat zur Bearbeitung seines Schwerpunktthemas „Nachwuchs“ für die Dauer der Kalenderjahre 2021-2022 eine Arbeitsgruppe eingerichtet – im Folgenden: AG Nachwuchs –, deren Aufgabe das Vorlegen eines umfassenden Berichts zur Situation der VWL-Promovierenden und -PostDocs im DACH-Raum ist. Gestützt auf Datenerhebungen und strukturierte Interviews formuliert die AG Nachwuchs in diesem Bericht zwei Empfehlungen, jeweils eine für den Doc- und den PostDoc-Bereich. Sie empfiehlt im PostDoc-Bereich, dass die Fakultäten bzw. verwandte VWL-Einrichtungen den Übergang zu Tenure-Track beschleunigen und ihn durch eine systematische Planung der Zahlenverhältnisse zwischen den Karrierestufen bei ihrem wissenschaftlichen Personal begleiten. Dadurch sollen bessere Karriereperspektiven erreicht werden. Sowohl die befragten Nachwuchskräfte als auch die befragten Professor:innen und Programmleitungen betonen die Thematik der Stellenperspektiven stark. Im Doc-Bereich dokumentieren die Erhebungsdaten eine überraschend geringe Zufriedenheit der VWL-Promovierenden mit der Betreuungssituation durch die Professorenschaft. Die AG Nachwuchs empfiehlt daher eine höhere Betreuungsdichte und eine stärkere Vernetzung von Promovierenden. Weitere Hilfestellungen für Promovierende können in Mehrfach- oder Teambetreuungen sowie in der Bereitstellung von Informationen über die Vielfalt möglicher Karrierewege bestehen.

GBP-Monitor Q3/2023: Das Wachstumschancengesetz – ein Investitionsimpuls? - Maiterth, Ralf; Sureth-Sloane, Caren; Dyck, Daniel; Heinemann-Heile, Vanessa (Schmalenbach IMPULSE)

Oh my Goodness: Investigating the Goodness of Performance Appraisal Formats Between and Within Teams - Gutt, Jana Kim; Mehic, Miro; Thommes, Kirsten (Academy of Management Proceedings)

Hegemoniale Spannungsfelder zwischen Judentum und Christentum. Beobachtungen zur Darstellung des christlich-jüdischen Verhältnisses in ausgewählten Religionsbüchern

Gottes Treue zu Israel bei Paulus - Woppowa, Jan; Taschl-Erber, Andrea (Elementare Bibeltexte (TLL Neuausgabe 2))

„… wie die Kinder in der Dritten Welt“ Postkoloniale und rassismuskritische Fragen an die Realisierung einer Didaktik des Perspektivenwechsels im Schulbuch - Woppowa, Jan; Drath, Hannah (Österreichisch-Religionspädagogisches Forum 31)

Konfessionelle Kooperation im Religionsunterricht weiterdenken: elementare Lernchancen und noch offene Fragen - Woppowa, Jan (Konfessionell – kooperativ – interreligiös. Liegt die Zukunft des Religionsunterrichts im Miteinander?)

Widerstand als Kategorie krisen- und differenzsensibler jüdischer Erwachsenenbildung nach 1933 - Woppowa, Jan (Katastrophen. Religiöse Bildung angesichts von Kriegs- und Krisenerfahrungen im 19. und 20. Jahrhundert)

Strategien konfessionsbezogener Kontingenzbewältigung – eine Response - Woppowa, Jan (Konfessionell – kooperativ – interreligiös. Liegt die Zukunft des Religionsunterrichts im Miteinander?)

Erfahrungen mit interreligiöser Kooperation im Religionsunterricht. Exemplarische Ein- und Ausblicke - Woppowa, Jan (Von der konfessionellen zur interreligiösen Kooperation im Religionsunterricht)

Religionsdidaktik in konfessionell-kooperativer Perspektive - Woppowa, Jan; Käbisch, David (Religionsunterricht weiterdenken. Innovative Ansätze für eine zukunftsfähige Religionsdidaktik)

Rassismus(kritik) im Religionsunterricht: Zur Auseinandersetzung mit der ‚rassistischen Normalität‘ im Kontext religiösen Lernens - Woppowa, Jan; Drath, Hannah (Religion 5-10)